The superior efficacy of anti-PD-1/PD-L1 immunotherapy in KRAS-mutant non-small cell lung cancer that correlates with an inflammatory phenotype and increased immunogenicity. (1st February 2020) - Liu, Chengming; Zheng, Sufei; Jin, Runsen; Wang, Xinfeng; Wang, Feng; Zang, Ruochuan; Xu, Haiyan; Lu, Zhiliang; Huang, Jianbing; Lei, Yuanyuan; Mao, Shuangshuang; Wang, Yalong; et al.
Abstract: Immune checkpoint inhibitors against PD-1/PD-L1 yield improved survival rates of KRAS-mutant NSCLC patients, who conferred a poor prognosis without effective targeted therapy until now. Yet, the underlying association between KRAS mutations and immune responses remains unclear. We performed an integrated analysis of the data from publicly available repositories and from clinical center cohorts to explore the association between KRAS mutation status and tumor immunity-associated features, including PD-L1 expression, CD8 + tumor-infiltrating lymphocytes (TILs) and tumor mutational burden (TMB). Our results revealed that KRAS mutations are correlated with an inflammatory tumor microenvironment and tumor immunogenicity, resulting in superior patient response to PD-1/PD-L1 inhibitors. Meanwhile, three-pool analysis further confirmed that KRAS-mutant NSCLC patients show remarkable clinical benefit from anti-PD-1/PD-L1 immunotherapy. In addition, a KRAS-mutant lung adenocarcinoma mouse model was established to estimate the relative efficacy of anti-PD-L1 monoclonal antibody monotherapy or combination treatment with docetaxel versus docetaxel alone. Most surprisingly, we found that PD-L1 blockade combined with docetaxel did not promote an anti-tumor response. These findings uncover that PD-1/PD-L1 blockade monotherapy may be the optimal therapeutic schedule in NSCLC patients harboring KRAS mutations. Highlights: KRAS mutation is correlated with an increased proportion of PD-L1 + /TIL + and may confer adaptive immune resistance. KRAS mutation promotes increased TMB and immunogenicity. PD-1/PD-L1 blockade monotherapy may be the optimal therapeutic schedule in NSCLC patients harboring KRAS mutation.